Well-being and emotional labor for preschool teachers: The mediation of career commitment and the moderation of social support - Xiaojie Su; Delin Yu; Yueyang Yu; Rong Lian (PLoS ONE, 2025)
Background According to the broaden-and-build theory of positive emotions, well-being is a protective factor against emotional labor. However, it is unclear whether and how well-being contributes to emotional labor for preschool teachers. To investigate the influence of well-being on emotional labor, this study aimed to examine the mediating effect of career commitment between preschool teachers' well-being and emotional labor and whether this effect is moderated by social support. Method This study included 363 preschool teachers (M = 30.17 years, SD = 5.94) in a Chinese province. All participants completed the General Well-Being Schedule, the Emotional Labor Strategy, the Career Commitment Scale, and the Social Support Rating Scale. The data were analyzed using SPSS 26.0. Results Correlation analysis revealed a significant positive relationship between well-being, career commitment, social support, and emotional labor. The results of path analysis show that career commitment plays a completely mediating role in the relationship between well-being and emotional labor, which is moderated by social support. The mediating effect of career commitment was significantly greater for individuals with high social support than for those with low social support. Conclusion Well-being can promote the emotional labor of preschool teachers by bolstering career commitment, while this process is influenced by social support.